2012
DOI: 10.1002/adfm.201200832
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelastic Strain Induced Antiferroelectric‐Ferroelectric Phase Transformation in Multilayer Thin Film Structures

Abstract: Coupling effects among mechanical, electrical and magnetic parameters in thin fi lm structures including ferroic thin fi lms provide exciting opportunity for creating device functionalities. For thin fi lms deposited on a substrate, their mechanical stress and microstructure are usually determined by the composition and processing of the fi lms and the lattice and thermal mismatch with the substrate. Here it is found that the stress and structure of an antiferroelectric (Pb 0.97 ,La 0.02 )(Zr 0.90 ,Sn 0.05 ,Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Accordingly, the AFE phases (see the double P-E loops in Fig. 5a), 5c) and 5e) will be well kept since the in-plane tensile stress is helpful to stabilize them in the PLZST thin films [46]. It should be noted that the residual stress also depends on the film orientation due to the anisotropic thermal expansion of the PLZST thin film [44].…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, the AFE phases (see the double P-E loops in Fig. 5a), 5c) and 5e) will be well kept since the in-plane tensile stress is helpful to stabilize them in the PLZST thin films [46]. It should be noted that the residual stress also depends on the film orientation due to the anisotropic thermal expansion of the PLZST thin film [44].…”
Section: Discussionmentioning
confidence: 93%
“…12,13 However, recent studies argued compressive strain could stabilize a FE phase in (001) pc -epitaxial PbZrO 3 thin films 14 and multilayer PZST films. 15 Recent theory calculations have suggested that AFE phase stability with strain is also related to the growth orientation of AFE films 16 and has been proven by experimental results from highly oriented polycrystalline PbZrO 3 films. 17 Previous studies, however, have focused on how AFE-FE phase transition and related polarization switching are affected by strain.…”
mentioning
confidence: 93%
“…Antiferroelectric (AFE) materials such as PbZrO 3 (PZO) and PZO-based materials exhibit many distinctive and useful properties, such as large electric-field (E-field) -induced strains, double-polarization-electric-field (P-E) hysteresis loops, and thermal/mechanical depolarization. These distinctive properties have many possible applications and have already led to the development of various devices, including potential generators, energy storage devices, and sensors [1][2][3][4][5][6][7]. The origin of these useful properties is associated with the distinctive structural transition between the AFE and FE phases induced by external stimuli such as E-field, mechanical force, and temperature [5,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A symmetry mode decomposition [19,20] of, for example, Corker et al's structure refinement [21] shows that the ground state of PZO is dominated by two large-amplitude primary modes. The first mode is associated with the modulation wave vector q 1 = [1/4,1/4,0] p (of 2 symmetry) and results in antiparallel displacements of A-site Pb 2+ and the neighboring apical O 2− ions along the resultant a, or [1][2][3][4][5][6][7][8][9][10] p , directions [of magnitudes 0.277 and 0.215Å, respectively; see Fig. 1(a)].…”
Section: Introductionmentioning
confidence: 99%